Assessment of the practices and challenges of value added tax administration: Case of Hawassa city revenue authority - Negash, Tekalign; Tamiru, Minase; Solomon, Esay (YAYASAN MITRA PERSADA NUSANTARA, 2025)
The study has focused on assessing the practice and key challenges that affect value-added tax administration in Hawassa city administration and identifying the areas of weakness and strength towards the achievement of the VAT objective. The study used a qualitative approach to collect and analyze both primary and secondary data. Descriptive research methods, probability proportional to size sampling techniques, percentages, tables, figures, and charts were employed to analyze the data by using Statistical Package for Social Science (SPSS) version 20 software. The study found that the main obstacles preventing revenue authority from producing what was initially planned during the administration of value-added tax are: a lack of sufficient numbers of skilled employees, limited staff capacity, non-responsiveness by the management, limited awareness creation, issues related to invoicing, and unfair competition and inflation which may negatively affects the performance of VAT administration. The study also highlights the requirement for improving the administration's capabilities in general and the value-added tax registration, assessment, and collection system in particular. To keep business enterprises informed, to improve taxpayer identification and registration, to reduce activities related to value-added tax evasion, and to provide efficient audit and enforcement systems, these authorities should regularly execute awareness-raising campaigns. The study will have implications for different stakeholders including but are not limited to resource providers (such as tax payers, donors, lender, and grantors), state and local governments, service recipients (like citizens at large) policy makers, legislature, audit committees, etc. in that, variables considered in the current studies are essential for issuing various regulations and proclamations hat enhance the VAT Revenue Collection of potentials of government and in turn uplift the living standards of the peoples.